Manufacturing Silage From Field Grass For Cattle Feed Using The Fermentation Method - Kiram, Jumadil; Zaini, Halim; Satriananda, S (Politeknik Negeri Lhokseumawe, 2023)
ABSTRACT Ruminant livestock require forage for growth, reproduction and production. The principle of forage for livestock is that it contains good nutrition and is available throughout the year. One technology for preserving forage is by making silage. Making silage, apart from preserving and minimizing nutrient loss, can also improve feed nutrition. Silage is feed that is preserved through the ensiling process, namely the process of preserving feed or forage using fermentation work under anaerobic conditions (Suadnyana, et al, 2017). In this research, field grass silage was made with the addition of EM4 containing Lactobacillus sp bacteria at different concentrations and varied fermentation times so that making field grass silage is expected to improve the fermentative quality and improve or maintain the nutritional quality of the feed which can be seen from the content. water, protein content, pH, and color. The analysis process was carried out with varying fermentation times of 4, 8, 12, 16 and 20 days and EM4 concentrations of 0.2%, 0.4%, 0.6% and 0.8% (v/w). The test results show that the best silage is with a fermentation time variation of 20 days with an EM4 concentration of 0.6%, 20 days with an EM4 concentration of 0.2%, and 16 days with an EM4 concentration of 0.8%. This is because the longer the fermentation time and the more EM4 added, the better the quality of the silage obtained. Keywords: EM4, Bran, Fermentation, Molasses, Silage